Se f(x)= raiz de 2x+3, então [f(raiz de 2) - f(- raiz de 2)]² é igual a:
Soluções para a tarefa
Respondido por
2
f(x) = √(2x+3)
[f(√2 - f(-√2)]² = ...
f(√2) = √(2√2+3) = √(√8+3)
f(-√2) = √(2.(-√2)+3) = √(-2√2+3) = √(-√8+3)
(√(√8+3))² - 2.√(√8+3).√(-√8+3) + (√(-√8+3))² =
(√8+3) - 2.(-8+3√8-3√8+9) - (√8+3) =
(√8+3) - (√8+3) - 2.(-8+9+3√8-3√8) =
-2.(1) = -2
[f(√2 - f(-√2)]² = ...
f(√2) = √(2√2+3) = √(√8+3)
f(-√2) = √(2.(-√2)+3) = √(-2√2+3) = √(-√8+3)
(√(√8+3))² - 2.√(√8+3).√(-√8+3) + (√(-√8+3))² =
(√8+3) - 2.(-8+3√8-3√8+9) - (√8+3) =
(√8+3) - (√8+3) - 2.(-8+9+3√8-3√8) =
-2.(1) = -2
Perguntas interessantes
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
Contabilidade,
1 ano atrás